Conformable fractional derivatives and applications to Newtonian dynamic and cooling body law - Parraga Cedeño, Pedro Abrahan (2022)
This article presents a rigorous review of the conformable fractional derivative given by J. E. Napoles in [11], studying its classical properties, as a differential operator. Likewise, applications are given to Physics, specifically to the free fall of bodies and Newton’s law of cooling.